Cross-Talk Between Gluten, Intestinal Microbiota and Intestinal Mucosa in Celiac Disease: Recent Advances and Basis of Autoimmunity - Chander, Atul Munish; Yadav, Hariom; Jain, Shalini; Bhadada, Sanjay Kumar; Dhawan, Devinder Kumar (Frontiers in Microbiology, 2018)
Celiac disease (CD) is an autoimmune disorder of the small intestine, caused by gluten induced inflammation in some individuals susceptible to genetic and environmental influences. To date, pathophysiology of CD in relation to intestinal microbiota is not known well. This review relies on contribution of intestinal microbiome and oral microbiome in pathogenesis of CD based on their interactions with gluten, thereby highlighting the role of upper gastrointestinal microbiota. It has been hypothesized that CD might be triggered by additive effects of immunotoxic gluten peptides and intestinal dysbiosis (microbial imbalance) in the people with or without genetic susceptibilities, where antibiotics may be deriving dysbiotic agents. In contrast to the intestinal dysbiosis, genetic factors even seem secondary in disease outcome thus suggesting the importance of interaction between microbes and dietary factors in immune regulation in intestinal mucosa. Moreover, association of imbalanced counts of some commensal microbes in intestine of CD patients suggests the scope for probiotic therapies. Lactobacilli and specific intestinal and oral bacteria are potent source of gluten degrading enzymes (glutenases) that may contribute to commercialization of a novel glutenase therapy. In this review, we shall discuss advantages and disadvantages of food based therapies along with probiotic therapies where probiotic therapies are expected to emerge as the safest biotherapies among other in-process therapies. In addition, this review emphasizes on differential targets of probiotics that make them suitable to manage CD as along with glutenase activity, they also exhibit immunomodulatory and intestinal microbiome modulatory properties.